Use of polymer-inorganic nanoparticle compositions as heat transfer fluids in battery or other electrical device systems

By using the polymer-inorganic nanoparticles as the heat transfer fluid, the problem of poor nanoparticle decentralization at high temperatures achieves high-efficiency thermal management and stability, and avoids copper corrosion.

CN114867816BActive Publication Date: 2025-01-28EVONIK OPERATIONS GMBH

Patent Information

Application Number
CN202080051597.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-07-17
Filing Date
2020-07-13
Publication Date
2025-01-28
Estimated Expiration
2040-07-13

AI Technical Summary

Technical Problem

The prior art is difficult to maintain sufficient dispersion of nanoparticles in the heat transfer fluid at high temperatures, resulting in low thermal management efficiency and poor stability of nanoparticles.

Method used

The polymer-inorganic nanoparticle composition is used as a heat transfer fluid, which is obtained by grinding a mixture, which contains nano particles of metal or quasi-metal oxides, nitride or carbides and polymer with specific structures.

Benefits of technology

Achieving the fully dispersing nanoparticles within high temperature for a long time, improving the thermal management efficiency and stability of thermal fluids, and avoiding copper corrosion and enhancing the load capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure QLYQS_1
    Figure QLYQS_1
  • Figure QLYQS_2
    Figure QLYQS_2
  • Figure QLYQS_3
    Figure QLYQS_3
Patent Text Reader

Abstract

The present invention relates to the use of polymer-inorganic nanoparticle compositions as heat transfer fluids in battery or other electrical device systems. The electrical devices may be, in particular, batteries, electric motors, electric vehicle transmissions, power transformers, capacitors, fluid-filled transmission lines, fluid-filled power cables, computers, and power electronics such as power converters.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the use of polymer-inorganic nanoparticle compositions as heat transfer fluids in battery or other electrical device systems. The electrical devices may be, in particular, batteries, electric motors, electric vehicle transmissions, power transformers, capacitors, fluid-filled transmission lines, fluid-filled power cables, computers, and power electronics such as power converters. Background Art

[0002] In recent years, energy shortages and environmental issues have had a huge impact on technological progress. Increased environmental awareness has led to a growing interest in so-called green technologies, particularly in the automotive industry. The demand for emission-free vehicles fueled by renewable energy, such as pure electric vehicles (EVs), hybrid electric vehicles (HEVs), and fuel cell electric vehicles, has gradually become more significant and is expected to increase dramatically in the next 20 years. The energy for such vehicles is provided and stored in batteries with high specific energy density. Various batteries can be used for EVs and HEVs, such as lead-acid, zinc / halogen, metal / air, sodium-β, nickel metal hydride (Ni-MH), and lithium ion (Li-ion).

[0003] To improve the performance of electric vehicles, large batteries with high current discharge are required. Due to their size and power output, these large batteries generate a lot of heat during rapid charge and discharge cycles at high current levels. Therefore, the battery must be thermally managed by cooling or heat dissipation to avoid battery failure and increase the life of the battery.

[0004] Furthermore, the performance of batteries is temperature-dependent. Depending on their type, batteries only perform optimally within a certain temperature range. Therefore, proper thermal management allows optimizing battery performance.

[0005] The review article by Naser Ali et al. (2018): "A review on nanofluids: fabrication, stability and thermophysical properties" deals with the development of nanofluids and states that the stability of nanofluids is a very important factor in the commercialization of nanofluids, as it prolongs the shelf life of the product while maintaining its thermo-physical properties. It also indicates that the main disadvantage of using this type of fluid is the increase in pressure losses in the piping system caused by the increased viscosity of the nanofluid. In this document, mainly hydrophilic heat transfer fluids are described as the prior art.

[0006] WO 2018 / 019783 A1 discloses a polymer-inorganic nanoparticle composition and a method for preparing the same, as well as its use in oil lubricant formulations to reduce pour point, friction and wear. WO 2018 / 019783 A1 does not involve heat transfer fluids.

[0007] US 2017 / 009120 A1 relates to a ready-to-use heat transfer fluid and a method for preventing corrosion in a heat transfer system, wherein the heat transfer fluid comprises a freezing point depressant, water, or a combination thereof; a carboxylate; an inorganic phosphate; an azole compound; calcium ions and / or magnesium ions; and a water-soluble polymer, such as a water-soluble acrylate polymer.

[0008] Kikuo Okuyama et al. (Ind. Eng. Chem. Res. 2008, 47, 2597-2604) describe polymer-nanoparticle composites in which titanium oxide is present in the monomer mixture during polymerization and is embedded in the resulting polymethyl methacrylate (PMMA), resulting in a solid TiO2-PMMA composite with improved UV light absorption properties.

[0009] WO 2019 / 107722 A1 discloses a heat radiation fluid composition comprising (i) a non-conductive oil, (ii) heat-conductive inorganic particles selected from silica, alumina, aluminosilicate, aluminum nitride, silicon nitride and boron nitride, and (iii) an inorganic precipitation inhibitor selected from fumed silica, fumed alumina or aerogel. In order to keep the inorganic nanoparticles fully dispersed in the heat transfer fluid, WO 2019 / 107722 A1 teaches a combination of controlled viscosity of the heat dissipation fluid, the use of an inorganic precipitation inhibitor and heat-conductive inorganic particles heavier than the inorganic precipitation inhibitor.

[0010] WO 2014 / 106556 A1 discloses the use of polyalkyl (meth)acrylates as heat transfer fluids. The composition in WO 2014 / 106556 A1 does not contain any inorganic nanoparticles. The polymer does not contain any functional monomer units.

[0011] WO 2013 / 115925 A1 discloses a nanocomposite fluid comprising a fluid medium and a nanoparticle composition containing nanoparticles, the nanoparticles being electrically insulating and thermally conductive. The document does not provide any specific examples of the preparation of the nanocomposite fluid. No details are provided on the stability of the nanocomposite fluid, nor are any viscosity and thermal conductivity comparisons with corresponding reference base fluids shown.

[0012] However, producing stable dispersions of nanoparticles is problematic. Most untreated inorganic nanoparticles, such as TiO2 and SiO2, are hydrophilic in nature and therefore form poor dispersions in oil or non-polar environments. In addition, poor dispersion of the particles and weak forces draw the particles together, causing agglomeration. These agglomerates will lead to sedimentation, which is undesirable and inefficient for formulation.

[0013] Therefore, the present invention is intended to provide in the electrical equipment (for example motor, electric vehicle transmission) with moving parts or in the electrical equipment (for example battery, power transformer, capacitor, fluid-filled transmission line, fluid-filled power cable, computer or power electronic equipment such as power converter) without any moving parts for the novel method of heat transfer.Usually, if it is possible to directly contact with metal parts, then hydrophobic dielectric fluid is preferred, and this provides electrical insulation, because they prevent electrical contact for safety reasons.Therefore, an object of the present invention is to provide the improved heat transfer nanofluid with the stability of nanoparticles increased in hydrophobic medium.Described heat transfer nanofluid should be stable in time and meet application standards, for example, when used in electrical equipment, has improved thermal properties under long time period and different temperatures. Summary of the invention

[0014] SUMMARY OF THE INVENTION

[0015] In the present invention, it was surprisingly found that the polymer-inorganic nanoparticle composition comprising inorganic nanoparticles and a polymer as defined in the present invention can be used as a heat transfer fluid for batteries and other electrical devices. The challenge is to combine large heat transfer performance while keeping the nanoparticles contained in the heat transfer fluid well dispersed for a long period of time at high temperature. The target use is achieved with the composition defined in the present invention.

[0016] According to a first aspect, the present invention thus relates to the use of a polymer-inorganic nanoparticle composition as defined in the present invention as a heat transfer fluid. The polymer-inorganic nanoparticle composition according to the present invention is advantageously used as a heat transfer fluid for electrical devices such as batteries, electric motors, electric vehicle transmissions, power transformers, capacitors, fluid-filled transmission lines, fluid-filled power cables, computers or power electronics such as power converters. DETAILED DESCRIPTION

[0017] Thus, the present invention relates to the use of a polymer-inorganic nanoparticle composition as a heat transfer fluid in a battery or other electrical device system, wherein the polymer-inorganic nanoparticle composition is obtainable by grinding a mixture comprising one or more inorganic nanoparticle compounds (A) and one or more polymer compounds (B),

[0018] (A) wherein the one or more inorganic nanoparticle compounds are selected from metal or metalloid oxide nanoparticles, metal or metalloid nitride nanoparticles, metal or metalloid carbide nanoparticles or mixtures thereof, and

[0019] (B) wherein the one or more polymer compounds are obtainable by polymerizing a monomer composition comprising:

[0020] a) 1 to 35 wt. % of one or more functional monomers selected from the list consisting of:

[0021] a1) aminoalkyl (meth)acrylates and (meth)acrylamides, for example N-(3-dimethylaminopropyl)methacrylamide, 2-dimethylaminoethyl (meth)acrylate, 3-diethylaminopentyl (meth)acrylate, 3-dibutylaminohexadecyl (meth)acrylate;

[0022] a2) nitriles of alkyl (meth) acrylic acid and other nitrogen-containing alkyl (meth) acrylic esters, such as N-(methacryloyloxyethyl) diisobutyl ketimine, N-(methacryloyloxyethyl) dihexadecyl-ketimine, (meth)acrylamidoacetonitrile, 2-methacryloyloxyethyl methyl cyanamide, cyanomethyl (meth) acrylate;

[0023] a3) (meth)acrylic esters of ether alcohols, such as tetrahydrofurfuryl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, 1-butoxypropyl (meth)acrylate, cyclohexyloxyethyl (meth)acrylate, propoxyethoxyethyl (meth)acrylate, benzyloxyethyl (meth)acrylate, furfuryl (meth)acrylate, 2-butoxyethyl (meth)acrylate, 2-ethoxy-2-ethoxyethyl (meth)acrylate, 2-methoxy-2-ethoxypropyl (meth)acrylate, ethoxylated (meth)acrylates, 1-ethoxybutyl (meth)acrylate, methoxyethyl (meth)acrylate, 2-ethoxy-2-ethoxy-2-ethoxyethyl (meth)acrylate, esters of (meth)acrylic acid and methoxypolyethylene glycol;

[0024] a4) Oxiranyl alkyl (meth)acrylates, such as 2,3-epoxybutyl (meth)acrylate, 3,4-epoxybutyl (meth)acrylate, 10,11-epoxyundecyl (meth)acrylate, 2,3-epoxycyclohexyl (meth)acrylate, 10,11-epoxyhexadecyl (meth)acrylate, glycidyl (meth)acrylate;

[0025] a5) alkyl (meth)acrylates containing phosphorus, boron and / or silicon, such as 2-(dimethylphosphato)propyl (meth)acrylate, 2-(ethylphosphino)propyl (meth)acrylate, 2-dimethylphosphinomethyl (meth)acrylate, dimethylphosphonoethyl (meth)acrylate, diethylmethacryloylphosphonate, dipropylmethacryloylphosphate, 2(dibutylphosphono)ethyl (meth)acrylate, 2,3-butylenemethacryloylethyl borate, methyldiethoxymethacryloylethoxysilane, diethylphosphatoethyl (meth)acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-(triethoxysilyl)propyl methacrylate, 3-(trichlorosilyl)propyl methacrylate;

[0026] a6) heterocycloalkyl (meth)acrylates, such as 2-(1-imidazolyl)ethyl (meth)acrylate, 2-(4-morpholinyl)ethyl (meth)acrylate, oxazolidinyl ethyl ester and N-methacryloyl morpholine;

[0027] a7) Vinyl halides, such as vinyl chloride, vinyl fluoride, vinylidene chloride and vinylidene fluoride;

[0028] a8) Vinyl esters such as vinyl acetate;

[0029] a9) vinyl monomers containing aromatic groups, such as styrene, substituted styrenes having alkyl substituents in the side chains, for example α-methylstyrene and α-ethylstyrene, substituted styrenes having alkyl substituents on the rings, for example vinyltoluene and p-methylstyrene, and halogenated styrenes such as monochlorostyrene, dichlorostyrene, tribromostyrene and tetrabromostyrene;

[0030] a10) Heterocyclic vinyl compounds, such as 2-vinylpyridine, 3-vinylpyridine, 2-methyl-5-vinylpyridine, 3-ethyl-4-vinylpyridine, 2,3-dimethyl-5-vinylpyridine, vinylpyrimidine, vinylpiperidine, 9-vinylcarbazole, 3-vinylcarbazole, 4-vinylcarbazole, 1-vinylimidazole, 2-methyl-1-vinylimidazole, N-vinylpyrrolidone, 2-vinylpyrrolidone, N-vinylpyrrolidine, 3-vinylpyrrolidine, N-vinylcaprolactam, N-vinylbutyrolactam, vinyloxolane, vinylfuran, vinylthiophene, vinylthiolane, vinylthiazole and hydrogenated vinylthiazole, vinyl Azoles and Hydrogenated Vinyl Azoles;

[0031] a11) vinyl and isoprenyl ethers;

[0032] a12) methacrylic acid and acrylic acid,

[0033] b) 65 to 99 weight percent, based on the total weight of the monomer composition, of one or more alkyl (meth)acrylate monomers, wherein each of the alkyl groups of the one or more alkyl (meth)acrylate monomers is independently linear, cyclic or branched and contains 1 to 40 carbon atoms, and

[0034] The weight ratio of the one or more inorganic nanoparticle compounds (A) to the one or more polymer compounds (B) is 9:1 to 1:5.

[0035] According to a preferred embodiment, the weight ratio of the one or more inorganic nanoparticle compounds (A) to the one or more polymer compounds (B) is preferably 9:1 to 1:2, more preferably 5:1 to 1:1, most preferably 3:1 to 1:1.

[0036] According to another preferred embodiment, the amounts of a) and b) add up to 100% by weight, based on the total weight of the monomer composition.

[0037] As used herein, "one or more" means that at least one or more than one of the components can be used as disclosed.

[0038] As used herein, "other electrical equipment systems" refers to electrical equipment such as batteries, electric motors, electric vehicle transmissions, power transformers, capacitors, fluid-filled drive lines, fluid-filled power cables, computers, or power electronics such as power converters.

[0039] The use defined above also refers to a method for enhancing heat transfer and thermal conductivity in a heat transfer fluid used in a battery or other electrical device system, wherein the polymer-inorganic nanoparticle composition is obtainable by grinding a mixture comprising one or more inorganic nanoparticle compounds (A) and one or more polymer compounds (B), as defined above and throughout the specification.

[0040] The heat transfer nanofluids according to the present invention show an increased stability of the nanoparticles in hydrophobic media, as demonstrated in the experimental part herein.

[0041] According to the present invention, it is preferred that the heat transfer fluid further comprises a base fluid (C) having a kinematic viscosity at 40°C of 3 to 30 cSt, more preferably 3 to 25 cSt according to ASTM D-445 and a flash point above 110°C according to ASTM D-93.

[0042] Advantageously, it has been observed that nanoparticle compositions used as heat transfer fluids in battery or other electrical equipment systems with metal moving parts not only enhance heat transfer and thermal conductivity, but also provide good tribological properties. The fluid can also be used as a lubricant having good tribological properties required in, for example, electric vehicle transmissions, but also in conventional internal combustion engine transmissions, particularly in manual transmissions, automated manual transmissions, automatic transmissions, continuously variable transmissions, and dual clutch transmissions in light and heavy applications. Additional good tribological properties include high load capacity without corrosion of copper, which is surprising and currently unattainable by using prior art chemicals. Using prior art chemicals, these two properties conflict with each other because sulfur-containing additives are necessary for high load capacity, and those sulfur-containing additives cause increased corrosion of copper by building copper sulfide. Avoiding copper corrosion is a requirement, particularly for EV applications, where direct contact of fluid with copper wires, circuit boards, and electrical connectors occurs. Using the composition of the present invention, load capacity can be enhanced without using components that cause copper corrosion. The experimental section illustrates these additional beneficial effects on load capacity while avoiding copper corrosion.

[0043] Therefore, in a preferred embodiment, when the nanoparticle composition used as a heat transfer fluid in a battery or other electrical device system has metal moving parts, the present invention is directed to a method for enhancing heat transfer and thermal conductivity, and for improving high load capacity while avoiding copper corrosion in a heat transfer fluid used in a battery or other electrical device system having metal moving parts.

[0044] Inorganic nanoparticle compound (A)

[0045] According to the present invention, inorganic nanoparticle compounds (also referred to herein as "particles" or "nanoparticles") are microscopic particles having at least one dimension of 1 to 500 nm, preferably 2 to 250 nm, more preferably 5 to 100 nm (measured using a transmission electron microscope TEM). Such particles may have individual characteristics or exist in aggregated and / or agglomerated structures. In the latter, the size of the primary particles is between the above sizes in at least one dimension. The size of the aggregated / agglomerated structure may be 50 to 100,000 nm, preferably 100 to 10,000 nm, more preferably 100 to 3,000 nm (measured using a static light scattering technique, d50 SLS).

[0046] All of the above dimensions are provided for illustrative purposes only and are not intended to limit the present disclosure.

[0047] According to a preferred aspect of the present invention, the inorganic nanoparticles are oxides, nitrides or carbides of silicon, cerium, titanium, aluminum, copper, calcium, magnesium, iron or zinc. Preferred metal or metalloid oxide nanoparticles are SiO2, CeO2, TiO2, Al2O3, CuO, CaO, MgO, Fe2O3, Fe3O4, ZnO or mixtures thereof. More preferably, the inorganic nanoparticles are TiO2 or Al2O3.

[0048] According to another preferred aspect of the present invention, the inorganic nanoparticles are selected from boron or aluminum nitrides, preferably hBN or AlN.

[0049] According to a preferred aspect of the present invention, the nanoparticles are selected from a mixture of the above structures.

[0050] According to another preferred aspect of the present invention, the nanoparticles are selected from TiO2, Al2O3 or a mixture thereof.

[0051] Polymer (B)

[0052] The polymers of the present invention are not crystalline or semi-crystalline polymers, but are amorphous polymers.

[0053] In a preferred embodiment of the present invention, the one or more polymer compounds (B) have a number average molecular weight (Mn) of 2,000 to 150,000 g / mol, more preferably 5,000 to 100,000 g / mol, even more preferably 5,000 to 80,000 g / mol.

[0054] In the present invention, the number average molecular weight of the polymer is determined by gel permeation chromatography (GPC) using polymethyl methacrylate (PMMA) calibration standards and tetrahydrofuran (THF) as eluent (flow rate: 1 ml / min; injection volume: 100 μl).

[0055] Preferably, the one or more polymer compounds (B) prepared with a monomer composition comprising monomer components a) and b) can be obtained by polymerizing a monomer composition comprising:

[0056] a) 1 to 30 wt%, more preferably 4 to 30 wt%, of one or more functional monomers as component a), based on the total weight of the monomer composition; and

[0057] b) 70 to 99 wt%, more preferably 70 to 96 wt%, of one or more alkyl (meth)acrylate monomers, wherein each alkyl group of the one or more alkyl (meth)acrylate monomers is independently linear, cyclic or branched and contains 1 to 40 carbon atoms, based on the total weight of the monomer composition.

[0058] In a preferred embodiment, the weight contents of monomers a) and b) of the monomer composition add up to 100% by weight, based on the total weight of the monomer composition.

[0059] Functionalized monomer a)

[0060] As already defined above, the one or more functional monomers a) according to the invention are selected from the list consisting of:

[0061] a1) aminoalkyl (meth)acrylates and aminoalkyl (meth)acrylamides;

[0062] a2) nitriles of alkyl(meth)acrylic acids and other nitrogen-containing alkyl(meth)acrylates;

[0063] a3) (meth)acrylates of ether alcohols;

[0064] a4) Oxiranyl alkyl (meth)acrylate;

[0065] a5) phosphorus-, boron- and / or silicon-containing alkyl (meth)acrylates;

[0066] a6) heterocycloalkyl (meth)acrylate;

[0067] a7) vinyl halides;

[0068] a8) vinyl esters;

[0069] a9) vinyl monomers containing aromatic groups;

[0070] a10) heterocyclic vinyl compounds;

[0071] a11) vinyl and prenyl ethers;

[0072] a12) Methacrylic acid and acrylic acid.

[0073] Preferably, the functional monomer a) is selected from aminoalkyl (meth)acrylates a1) or aminoalkyl (meth)acrylamides a1) or silicon-containing alkyl (meth)acrylates a5) or heterocycloalkyl (meth)acrylates a6). More preferably, it is selected from aminoalkyl (meth)acrylates a1) or aminoalkyl (meth)acrylamides a1) or heterocycloalkyl (meth)acrylates a6).

[0074] Even more preferably, the functionalized monomer a) is selected from N-(3-dimethyl-aminopropyl)methacrylamide, 2-dimethylaminoethyl (meth)acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-(triethoxysilyl)propyl methacrylate or (meth)acrylate. Oxazolidinyl ethyl ester, most preferably selected from N-(3-dimethyl-aminopropyl)methacrylamide, 2-dimethylaminoethyl (meth)acrylate or (meth)acrylate Oxazolidinyl ethyl ester.

[0075] Alkyl (meth) acrylate monomer b)

[0076] The term "(meth)acrylic acid" refers to acrylic acid, methacrylic acid, and mixtures of acrylic acid and methacrylic acid; methacrylic acid is preferred. The term "(meth)acrylate" refers to esters of acrylic acid, esters of methacrylic acid, or mixtures of esters of acrylic acid and methacrylic acid; esters of methacrylic acid are preferred.

[0077] The term "(meth)acrylic acid" 1-40 "Alkyl esters" refers to esters of (meth)acrylic acid and straight chain, cyclic or branched alcohols containing 1 to 40 carbon atoms. The term encompasses individual (meth)acrylic esters of alcohols of a particular length, and also encompasses mixtures of (meth)acrylic esters with alcohols of different lengths.

[0078] According to the present invention, it is preferred that in optional component b) of the polymer-inorganic nanoparticle composition, each alkyl group of the one or more alkyl (meth)acrylate monomers is independently linear, cyclic or branched and contains 1 to 40 carbon atoms.

[0079] According to the present invention, preferably the one or more alkyl (meth)acrylate monomers b) comprise:

[0080] b1) one or more alkyl (meth)acrylates of formula (I):

[0081]

[0082] Where R is hydrogen or methyl, R 1 means a linear, branched or cyclic alkyl residue containing 1 to 8 carbon atoms, preferably 1 to 5 carbon atoms, more preferably 1 to 4 carbon atoms, based on the total weight of the monomer composition,

[0083] b2) one or more alkyl (meth)acrylates of formula (II):

[0084]

[0085] Where R is hydrogen or methyl, R 2 means a linear, branched or cyclic alkyl radical containing 9 to 15 carbon atoms, preferably 12 to 15 carbon atoms,

[0086] b3) one or more alkyl (meth)acrylates of formula (III):

[0087]

[0088] Where R is hydrogen or methyl, R 3 It means a linear, branched or cyclic alkyl residue containing 16 to 40 carbon atoms, preferably 16 to 30 carbon atoms, more preferably 16 to 22 carbon atoms.

[0089] The term "(meth)acrylic acid" 1-8 "Alkyl esters" refers to esters of (meth)acrylic acid and straight-chain or branched alcohols containing 1 to 8 carbon atoms. The term encompasses individual (meth)acrylic esters of an alcohol of a particular length, and also encompasses mixtures of (meth)acrylic esters with alcohols of different lengths.

[0090] According to the present invention, each of the one or more monomers according to formula (I), namely (meth)acrylic acid C 1-8 The alkyl esters may be independently selected from (meth)acrylates derived from saturated alcohols, preferably methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, isopropyl (meth)acrylate, n-butyl (meth)acrylate, tert-butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, cycloalkyl (meth)acrylate, cyclopentyl (meth)acrylate, cyclohexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, heptyl (meth)acrylate, 2-tert-butylheptyl (meth)acrylate, n-octyl (meth)acrylate and 3-isopropylheptyl (meth)acrylate, the most preferred monomer according to formula (II) being methyl methacrylate.

[0091] Particularly preferred (meth)acrylic acid C 1-8 Alkyl esters are methyl (meth)acrylate and n-butyl (meth)acrylate; methyl methacrylate and n-butyl methacrylate are particularly preferred.

[0092] The term "(meth)acrylic acid" 9-15 "Alkyl esters" refers to esters of (meth)acrylic acid and straight-chain or branched alcohols containing 9 to 15 carbon atoms. The term encompasses individual (meth)acrylic esters of an alcohol of a particular length, and also encompasses mixtures of (meth)acrylic esters with alcohols of different lengths.

[0093] According to the present invention, each of the one or more monomers according to formula (II), namely (meth)acrylic acid C 9-15The alkyl esters may also be independently selected from nonyl (meth)acrylate, decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, 5-methylundecyl (meth)acrylate, n-dodecyl (meth)acrylate, 2-methyldodecyl (meth)acrylate, tridecyl (meth)acrylate, 5-methyltridecyl (meth)acrylate, n-tetradecyl (meth)acrylate, pentadecyl (meth)acrylate, oleyl (meth)acrylate, cycloalkyl (meth)acrylate, cyclohexyl (meth)acrylate having a ring substituent, tert-butylcyclohexyl (meth)acrylate, trimethylcyclohexyl (meth)acrylate, bornyl (meth)acrylate and isobornyl (meth)acrylate.

[0094] Particularly preferred (meth)acrylic acid C 9-15 Alkyl esters are linear C 12-14 (Meth) acrylic acid esters of alcohol mixtures ((meth) acrylic acid C 12-14 Alkyl esters-lauryl methacrylate-LMA) or linear C 12-15 (Meth) acrylic acid esters of alcohol mixtures ((meth) acrylic acid C 12-15 Alkyl esters-dodecyl pentadecyl methacrylate-DPMA).

[0095] The term "(meth)acrylic acid" 16-40 "Alkyl esters" refers to esters of (meth)acrylic acid and straight-chain or branched alcohols containing 16 to 40 carbon atoms. The term encompasses individual (meth)acrylic esters of an alcohol of a particular length, and also encompasses mixtures of (meth)acrylic esters with alcohols of different lengths.

[0096] According to the present invention, each of the one or more monomers according to formula (III), namely (meth)acrylic acid C 16-40The alkyl esters may also be independently selected from hexadecyl (meth)acrylate, 2-methylhexadecyl (meth)acrylate, heptadecyl (meth)acrylate, 5-isopropylheptadecyl (meth)acrylate, 4-tert-butyloctadecyl (meth)acrylate, 5-ethyloctadecyl (meth)acrylate, 3-isopropyloctadecyl (meth)acrylate, octadecyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, cetyl eicosyl (meth)acrylate, stearyl eicosyl (meth)acrylate, behenyl (meth)acrylate, eicosyl tetratriadecyl (meth)acrylate, cycloalkyl (meth)acrylate, 2,4,5-tri-tert-butyl-3-vinylcyclohexyl (meth)acrylate and 2,3,4,5-tetra-tert-butylcyclohexyl (meth)acrylate.

[0097] Preferred monomer compositions

[0098] According to a preferred embodiment of the present invention, preferably the one or more polymer compounds (B) are obtainable by polymerizing a monomer composition comprising the following components:

[0099] a) 1 to 35 wt%, more preferably 1 to 30 wt%, even more preferably 4 to 30 wt% of one or more functionalized monomers as component a), based on the total weight of the monomer composition; and

[0100] b1) 0 to 20 wt%, more preferably 0 to 15 wt%, of one or more alkyl (meth) acrylate monomers of formula (I) as first component b), wherein each alkyl group of the one or more alkyl (meth) acrylate monomers is independently linear, cyclic or branched and contains 1 to 8 carbon atoms, preferably 1 to 5 carbon atoms, more preferably 1 to 4 carbon atoms, based on the total weight of the monomer composition; and

[0101] b2) 45 to 99 wt. %, more preferably 50 to 96 wt. %, of one or more alkyl (meth) acrylate monomers of formula (II), as the second component b), wherein each alkyl group of the one or more alkyl (meth) acrylate monomers is independently linear, cyclic or branched and contains 9 to 15 carbon atoms, preferably 12 to 15 carbon atoms, based on the total weight of the monomer composition; and

[0102] b3) 0 to 30 wt. %, more preferably 0 to 20 wt. %, of one or more alkyl (meth) acrylate monomers of formula (III), as the third component b), wherein each alkyl group of the one or more alkyl (meth) acrylate monomers is independently linear, cyclic or branched and contains 16 to 40 carbon atoms, preferably 16 to 30 carbon atoms, more preferably 16 to 22 carbon atoms, based on the total weight of the monomer composition;

[0103] The amounts of all monomers in the monomer composition add up to 100% by weight.

[0104] According to another preferred embodiment of the present invention, it is preferred that the one or more polymer compounds (B) are obtainable by polymerizing a monomer composition comprising the following components:

[0105] a) 1 to 35 wt. %, more preferably 1 to 30 wt. %, even more preferably 4 to 30 wt. % of aminoalkyl(meth)acrylate a1) or aminoalkyl(meth)acrylamide a1) or silicon-containing alkyl(meth)acrylate a5) or heterocycloalkyl(meth)acrylate a6) as component a), based on the total weight of the monomer composition;

[0106] b1) 0 to 20 wt. % of one or more alkyl (meth) acrylate monomers of formula (I) as first component b), wherein each alkyl group of the one or more alkyl (meth) acrylate monomers is independently linear, cyclic or branched and contains 1 to 8 carbon atoms, preferably 1 to 5 carbon atoms, more preferably 1 to 4 carbon atoms, based on the total weight of the monomer composition; and

[0107] b2) 45 to 99 wt. %, more preferably 50 to 96 wt. %, of one or more alkyl (meth) acrylate monomers of formula (II), as the second component b), wherein each alkyl group of the one or more alkyl (meth) acrylate monomers is independently linear, cyclic or branched and contains 9 to 15 carbon atoms, preferably 12 to 15 carbon atoms, based on the total weight of the monomer composition; and

[0108] b3) 0 to 30 wt. %, more preferably 0 to 20 wt. %, of one or more alkyl (meth) acrylate monomers of formula (III), as the third component b), wherein each alkyl group of the one or more alkyl (meth) acrylate monomers is independently linear, cyclic or branched and contains 16 to 40 carbon atoms, preferably 16 to 30 carbon atoms, more preferably 16 to 22 carbon atoms, based on the total weight of the monomer composition;

[0109] The amounts of all monomers in the monomer composition add up to 100% by weight.

[0110] In another particularly preferred embodiment of the present invention, the one or more polymer compounds (B) are obtainable by polymerizing a monomer composition comprising:

[0111] a1) 1 to 10 wt %, more preferably 1 to 5 wt %, based on the total weight of the monomer composition, of aminoalkyl(meth)acrylamide, most preferably N-(3-dimethylaminopropyl)methacrylamide, as component a); and

[0112] b1) 0 to 15 wt %, more preferably 0 to 10 wt %, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (I), most preferably methyl methacrylate, as a first component b); and

[0113] b2) 80 to 99 wt %, more preferably 90 to 99 wt %, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (II), most preferably lauryl methacrylate or dodecyl pentadecyl methacrylate, as second component b);

[0114] The amounts of all monomers in the monomer composition add up to 100% by weight.

[0115] In another particularly preferred embodiment of the present invention, the one or more polymer compounds (B) are obtainable by polymerizing a monomer composition comprising:

[0116] a1) 10 to 35 wt %, more preferably 20 to 35 wt %, based on the total weight of the monomer composition, of an aminoalkyl (meth)acrylate, most preferably 2-dimethylaminoethyl (meth)acrylate, as component a); and

[0117] b1) 0 to 10 wt %, more preferably 0 to 5 wt %, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (I), most preferably methyl methacrylate and / or butyl methacrylate, as a first component b); and

[0118] b2) 45 to 80 wt%, more preferably 45 to 55 wt%, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (II), most preferably lauryl methacrylate or dodecyl pentadecyl methacrylate, as second component b);

[0119] b3) 10 to 30 wt %, more preferably 10 to 20 wt %, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (III), most preferably stearyl eicosyl methacrylate, as the third component b);

[0120] The amounts of all monomers in the monomer composition add up to 100% by weight.

[0121] In another particularly preferred embodiment of the present invention, the one or more polymer compounds (B) are obtainable by polymerizing a monomer composition comprising:

[0122] a5) 1 to 20 wt%, more preferably 5 to 15 wt%, based on the total weight of the monomer composition, of a silicon-containing alkyl (meth)acrylate, most preferably 3-(trimethoxysilyl)propyl methacrylate, as component a); and

[0123] b2) 80 to 99 wt %, more preferably 85 to 95 wt %, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (II), most preferably lauryl methacrylate, as the second component b);

[0124] The amounts of all monomers in the monomer composition add up to 100% by weight.

[0125] In another particularly preferred embodiment of the present invention, the one or more polymer compounds (B) are obtainable by polymerizing a monomer composition comprising:

[0126] a6) 1 to 15 wt %, more preferably 1 to 10 wt %, based on the total weight of the monomer composition, of a heterocyclic (meth)acrylate, most preferably (meth)acrylate Oxazolidinyl ethyl ester, as component a); and

[0127] b1) 0 to 20 wt%, more preferably 10 to 20 wt%, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (I), most preferably methyl methacrylate, as a first component b); and

[0128] b2) 65 to 99 wt %, more preferably 70 to 89 wt %, based on the total weight of the monomer composition, of an alkyl (meth)acrylate monomer of formula (II), most preferably lauryl methacrylate, as the second component b);

[0129] The amounts of all monomers in the monomer composition add up to 100% by weight.

[0130] Preparation of polymer compound (B)

[0131] According to the present invention, the above polymer can be prepared according to a method comprising the following steps:

[0132] (x) providing the above-mentioned monomer composition; and

[0133] (y) initiating free radical polymerization in the monomer composition.

[0134] Standard free-radical polymerization is described in detail in, inter alia, Ullmann's Encyclopedia of Industrial Chemistry, 6th Edition. Typically, polymerization initiators and, optionally, chain transfer agents are used for this purpose.

[0135] The polymerization can be carried out under standard pressure, reduced pressure or elevated pressure. The polymerization temperature is also not critical. However, typically, it is in the range of -20 to 200°C, preferably 50 to 150°C, more preferably 80 to 130°C.

[0136] The polymerization step (y) can be carried out with or without dilution in oil. If dilution is carried out, the amount of the monomer composition, i.e. the total amount of monomers, is preferably 20 to 90 wt %, more preferably 40 to 80 wt %, most preferably 50 to 70 wt % relative to the total weight of the reaction mixture.

[0137] Preferably, the oil used to dilute the monomer mixture is an API Group I, II, III, IV or V oil or a mixture thereof. Preferably, a Group III oil or a mixture thereof is used to dilute the monomer mixture.

[0138] Preferably, step (y) comprises adding a free radical initiator.

[0139] Suitable free radical initiators are, for example, azo initiators, such as azobisisobutyronitrile (AIBN), 2,2'-azobis(2-methylbutyronitrile) (AMBN) and 1,1-azobiscyclohexanecarbonitrile, and peroxide compounds, such as methyl ethyl ketone peroxide, acetylacetone peroxide, dilauryl peroxide, tert-butyl per-2-ethylhexanoate, ketone peroxide, tert-butyl peroctoate, methyl isobutyl ketone peroxide, cyclohexanone peroxide, dibenzoyl peroxide, tert-butyl peroxybenzoate, dimethicone peroxide ... tert-Butyl isopropyl carbonate, 2,5-bis(2-ethylhexanoylperoxy)-2,5-dimethylhexane, tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroxy-3,5,5-trimethylhexanoate, dicumyl peroxide, 1,1-bis(tert-butylperoxy)cyclohexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, cumyl hydroperoxide, tert-butyl hydroperoxide, tert-butyl peroxypivalate and bis(4-tert-butylcyclohexyl) peroxydicarbonate.

[0140] Preferably, the free radical initiator is selected from 2,2'-azobis(2-methylbutyronitrile), 2,2-bis(tert-butylperoxy)butane, tert-butylperoxy-2-ethylhexanoate, 1,1-di-tert-butylperoxy-3,3,5-trimethylcyclohexane, tert-butyl peroctanoate, tert-butyl peroxybenzoate, tert-butyl peroxypivalate and tert-butyl peroxy-3,5,5-trimethylhexanoate. Particularly preferred initiators are tert-butyl peroxy-2-ethylhexanoate, tert-butyl peroctanoate and tert-butyl peroxypivalate.

[0141] Preferably, the total amount of free radical initiator is from 0.01 to 5 wt%, more preferably from 0.1 to 3 wt%, most preferably from 0.1 to 2 wt%, relative to the total weight of the monomer mixture.

[0142] The total amount of free radical initiator can be added in a single step, or the free radical initiator can be added in several steps during the polymerization reaction. Preferably, the free radical initiator is added in several steps. For example, a portion of the free radical initiator can be added to initiate free radical polymerization, and a second portion of the free radical initiator can be added 0.5 to 3.5 hours after the initial dose.

[0143] Preferably, step (y) further comprises the addition of a chain transfer agent. Suitable chain transfer agents are in particular oil-soluble mercaptans, for example n-dodecyl mercaptan, 2-ethylhexyl thioglycolate or 2-mercaptoethanol or chain transfer agents from the class of terpenes, for example terpinolene. The addition of n-dodecyl mercaptan and 2-ethylhexyl thioglycolate is particularly preferred.

[0144] The monomer composition can also be divided into an initial portion and a second portion, and a portion of the free radical initiator is added only to the initial portion to start the polymerization reaction therein. Then, the second portion of the free radical initiator is added to the second portion of the monomer composition, and then added to the polymerization mixture over a period of 0.5 to 5 hours, preferably 1.5 to 4 hours, more preferably 2 to 3.5 hours. After adding the second monomer mixture, the third portion of the free radical initiator can be added to the polymerization reaction as described above.

[0145] Preferably, the total reaction time of the free radical polymerization is from 2 to 10 hours, more preferably from 3 to 9 hours.

[0146] After the free radical polymerization is complete, the resulting polymer is preferably further diluted with the above oil to the desired viscosity. Preferably, the polymer is diluted to a concentration of 5 wt % to 60 wt % polymer, more preferably 10 wt % to 50 wt %, most preferably 20 wt % to 40 wt %.

[0147] Polymer-inorganic nanoparticle composition of the present invention

[0148] According to a preferred embodiment of the present invention, the polymer-inorganic nanoparticle composition comprising one or more nanoparticles (A) and one or more polymer compounds (B) as defined herein may further comprise a base fluid (C) having a kinematic viscosity at 40°C of 3 cSt to 30 cSt, more preferably 3 cSt to 25 cSt according to ASTM D-445 and a flash point above 110°C according to ASTM D-93.

[0149] The base fluid (C) may be a base oil selected from the list consisting of API Group I base oils, API Group II base oils, API Group III, API Group IV base oils, and API Group V base oils, or a combination thereof.

[0150] Base oils may also be defined as specified by the American Petroleum Institute (API) (see "Appendix E—API Base Oil Interchangeability Guidelines for Passenger Car Motor Oils and Diesel Engine Oils", April 2008 edition, Section 1.3, Subheading 1.3. "Base Stock Categories").

[0151] API currently defines five groups of lubricant base stocks (API 1509, Appendix E - API Base Oil Interchangeability Guidelines for Passenger Car Motor Oils and Diesel Engine Oils, September 2011). Groups I, II and III are mineral oils, which are classified by the amount of saturates and sulfur they contain and by their viscosity index; Group IV is polyalphaolefins; Group V is all others, including, for example, ester oils. The following table shows these API classifications.

[0152] Table 1 - API Definition of Lubricant Base Stocks

[0153]

[0154] In a preferred embodiment, the base fluid (C) having a kinematic viscosity at 40°C of 3 cSt to 30 cSt, more preferably 3 cSt to 25 cSt according to ASTM D-445 and a flash point above 110°C according to ASTM D-93 is selected from polyalphaolefins, tetrabutane, API Group III base oils or mixtures thereof; preferably, tetrabutane or API Group III base oils, or mixtures thereof.

[0155] The base fluid (C) may be a fluorinated compound such as polyhexafluoropropylene oxide, perfluoropolyether (PFPE), perfluoroalkyl ether (PFAE), perfluoropolyalkyl ether (PFPAE), hydrofluoroether or a mixture thereof.

[0156] If the base fluid (C) is selected from API Group V base oils, it is preferably selected from silicone oils, cycloparaffins, polyalkylene glycols, synthetic oils (including liquid esters of phosphoric acid) or mixtures thereof.

[0157] The base fluid (C) may also be a mixture of any of the base oils listed above.

[0158] Preferably, the nanoparticle composition used as a heat transfer fluid comprises 80 to 99.9 wt% of the base fluid (C) and 0.1 to 20 wt% of (A) and (B), more preferably 85 to 99.9 wt% of the base fluid (C) and 0.1 to 15 wt% of (A) and (B), most preferably 88 to 99.5 wt% of the base fluid (C) and 0.5 to 12 wt% of (A) and (B), based on the total weight of the polymer-inorganic nanoparticle composition. In another preferred embodiment, the amounts of (A), (B) and (C) total 100 wt%, based on the total weight of the polymer-inorganic nanoparticle composition.

[0159] In a preferred embodiment of the method for producing a polymer-inorganic nanoparticle composition, a mixture of one or more inorganic nanoparticles (A), one or more polymer compounds (B) and optionally, a base fluid (C) is ground using an ultrasonic device having a power of 10 to 1000 W, preferably 50 to 800 W, more preferably 100 to 500 W. Preferably, the composition is ground for 1 to 240 minutes, more preferably 10 to 180 minutes, even more preferably 30 to 150 minutes to obtain a stable polymer-inorganic nanoparticle composition.

[0160] In another preferred embodiment, a mixture of one or more inorganic nanoparticles (A), one or more polymer compounds (B) and optionally a base fluid (C) is ground using ultrahigh pressure technology (e.g. jet milling equipment SuginoUltimaizer HJP-25050). At least two streams of this mixture are each jetted into a grinding chamber enclosed by a reactor housing via a nozzle (diameter 0.25 mm) to the point of collision using a pump, preferably a high-pressure pump, characterized in that the grinding chamber is filled with the mixture and the final ground mixture is removed from the grinding chamber by the overpressure of the continuous stream entering the grinding chamber. The pump pressure is 100 to 4000 bar, preferably 400 to 3000 bar, more preferably 1000 to 2500 bar.

[0161] According to another preferred embodiment, the polymer-inorganic nanoparticle composition comprising one or more inorganic nanoparticles (A), one or more polymer compounds (B) and optionally, a base fluid (C) is ground via a ball milling process. Preferably, the ball milling process comprises introducing 0.1 to 10 kWh / kg, preferably 1 to 5 kWh / kg, more preferably 1.5 to 3 kWh / kg of energy into the mixture.

[0162] In another preferred embodiment, the method for making a polymer-inorganic nanoparticle composition, in particular a polymer-inorganic nanoparticle composition as described above, comprises the following steps:

[0163] (i) providing one or more inorganic nanoparticle compounds (A) as defined herein;

[0164] (ii) providing one or more polymer compounds (B) as defined herein;

[0165] (iii) preferably providing a base fluid (C) as defined herein;

[0166] (iv) combining at least one or more inorganic nanoparticle compounds (A) and one or more polymer compounds (B) to obtain a mixture, preferably combining at least one or more inorganic nanoparticle compounds (A), one or more polymer compounds (B) and a base fluid (C) to obtain a mixture; and

[0167] (v) grinding the mixture.

[0168] According to the present invention, the grinding step (v) is defined by the resulting change in the particle size distribution of the polymer-inorganic nanoparticle composition measured using the dynamic light scattering technique (DLS).

[0169] The grinding technique according to the invention described in step (v) can be a dissolver, a rotor-stator device, homogenization, high pressure homogenization, high shear mixing, ultrasound, ball milling or ultrahigh pressure technology (jet milling) or a combination thereof. In fact, the particle size of the agglomerates is reduced using these grinding techniques.

[0170] The most preferred embodiment is to mill the mixture via ultra-high pressure technology (jet milling).

[0171] The heat transfer fluid according to the present invention may also contain other additives as component (D) selected from the following substances: dispersants, defoamers, seal fixatives or seal compatibilizers, detergents, antioxidants, metal passivators, rust inhibitors, static discharge inhibitors, demulsifiers, emulsifiers, pour point depressants, anti-wear additives, extreme pressure additives, corrosion inhibitors, friction modifiers, dyes and mixtures thereof, as discussed below.

[0172] Suitable dispersants include poly(isobutylene) derivatives, such as poly(isobutylene) succinimide (PIBSI), including borated PIBSI; and ethylene-propylene oligomers having N / O functional groups.

[0173] Dispersants (including borated dispersants) are preferably used in an amount of 0 to 10 wt %, based on the total weight of the polymer-inorganic nanoparticle composition.

[0174] Suitable defoamers are silicone oils, fluorosilicone oils or fluoroalkyl ethers.

[0175] The defoaming agent is preferably used in an amount of 0.005 wt% to 0.5 wt% based on the total weight of the polymer-inorganic nanoparticle composition.

[0176] Preferred detergents include metal-containing compounds, such as phenates; salicylates; thiophosphonates, in particular thiopyrophosphonates, thiophosphonates and phosphonates; sulfonates and carbonates. As metals, these compounds may contain in particular calcium, magnesium and barium. These compounds may preferably be used in neutral or overbased form.

[0177] The detergent is preferably used in an amount of 0.2 to 5 wt % based on the total weight of the polymer-inorganic nanoparticle composition.

[0178] Suitable antioxidants include, for example, phenol-based antioxidants and amine-based antioxidants.

[0179] Phenol-based antioxidants include, for example, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; 4,4'-methylenebis(2,6-di-tert-butylphenol); 4,4'-bis(2,6-di-tert-butylphenol); 4,4'-bis(2-methyl-6-tert-butylphenol); 2,2'-methylenebis(4-ethyl-6-tert-butylphenol); 2,2'-methylenebis(4-methyl -6-tert-butylphenol); 4,4'-butylidenebis(3-methyl-6-tert-butylphenol); 4,4'-isopropylidenebis(2,6-di-tert-butylphenol); 2,2'-methylenebis(4-methyl-6-nonylphenol); 2,2'-isobutylidenebis(4,6-dimethylphenol); 2,2'-methylenebis(4-methyl-6-cyclohexylphenol); 2,6-di-tert-butyl-4-methylphenol ; 2,6-di-tert-butyl-4-ethyl-phenol; 2,4-dimethyl-6-tert-butylphenol; 2,6-di-tert-amyl-p-cresol; 2,6-di-tert-butyl-4-(N,N'-dimethylaminomethylphenol); 4,4'-thiobis(2-methyl-6-tert-butylphenol); 4,4'-thiobis(3-methyl-6-tert-butylphenol); 2,2'-thiobis(4-methyl-6-tert-butylphenol); phenol); bis(3-methyl-4-hydroxy-5-tert-butylbenzyl) sulfide; bis(3,5-di-tert-butyl-4-hydroxybenzyl) sulfide; n-octyl-3-(4-hydroxy-3,5-di-tert-butylphenyl) propionate; n-octadecyl-3-(4-hydroxy-3,5-di-tert-butylphenyl) propionate; 2,2'-thio[diethyl-bis-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]. Among them, particularly preferred are bisphenol-based antioxidants and ester-containing phenol-based antioxidants.

[0180] Amine-based antioxidants include, for example, monoalkyldiphenylamines such as monooctyldiphenylamine and monononyldiphenylamine; dialkyldiphenylamines such as 4,4'-dibutyldiphenylamine, 4,4'-dipentyldiphenylamine, 4,4'-dihexyldiphenylamine, 4,4'-diheptyldiphenylamine, 4,4'-dioctyldiphenylamine and 4,4'-dinonyldiphenylamine; polyalkyldiphenylamines such as tetrabutyldiphenylamine, tetrahexyldiphenylamine, tetraoctyldiphenylamine and tetranonyldiphenylamine; naphthylamines, specifically α-naphthylamine, phenyl-α-naphthylamine and other alkyl-substituted phenyl-α-naphthylamines such as butylphenyl-α-naphthylamine, pentylphenyl-α-naphthylamine, hexylphenyl-α-naphthylamine, heptylphenyl-α-naphthylamine, octylphenyl-α-naphthylamine and nonylphenyl-α-naphthylamine. Among them, diphenylamine is preferred over naphthylamine from the viewpoint of its antioxidant effect.

[0181] Suitable antioxidants may further be selected from: sulfur- and phosphorus-containing compounds, such as metal dithiophosphates, for example zinc dithiophosphate (ZnDTP), "OOS triesters" = reaction products of dithiophosphoric acid with activated double bonds from olefins, cyclopentadiene, norbornadiene, α-pinene, polybutene, acrylates, maleates (ashless when burned); organic sulfur compounds, such as dialkyl sulfides, diaryl sulfides, polysulfides, modified mercaptans, thiophene derivatives, xanthates, thiodiols, thioaldehydes, sulfur-containing carboxylic acids; heterocyclic sulfur / nitrogen compounds, especially dialkyldimercaptothiadiazoles, 2-mercaptobenzimidazoles; zinc bis(dialkyldithiocarbamates) and methylenebis(dialkyldithiocarbamates); organic phosphorus compounds, such as triaryl and trialkyl phosphites; organic copper compounds and overbased calcium and magnesium phenolates and salicylates.

[0182] The antioxidant is used in an amount of 0 to 15 wt %, preferably 0.1 to 10 wt %, more preferably 0.2 to 5 wt %, based on the total weight of the polymer-inorganic nanoparticle composition.

[0183] Pour point depressants include ethylene-vinyl acetate copolymers, chlorinated paraffin-naphthalene condensates, chlorinated paraffin-phenol condensates, polymethacrylates, polyalkylstyrenes. Preferred are polymethacrylates having a weight average molecular weight (Mw) of 5,000 to 200,000 g / mol.

[0184] The amount of pour point depressant is preferably 0.1 to 5 wt %, based on the total weight of the polymer-inorganic nanoparticle composition.

[0185] Preferred antiwear and extreme pressure additives include sulfur-containing compounds such as zinc dithiophosphate, di-C 3-12 Zinc alkyl dithiophosphates (ZnDTPs), zinc phosphates, zinc dithiocarbamates, molybdenum dithiocarbamates, molybdenum dithiophosphates, disulfides, sulfurized olefins, sulfurized oils and fats, sulfurized esters, thiocarbonates, thiocarbamates, polysulfides; phosphorus-containing compounds such as phosphites, phosphates, for example trialkyl phosphates, triaryl phosphates, for example tricresyl phosphate, amine-neutralized monoalkyl and dialkyl phosphates, ethoxylated monoalkyl and dialkyl phosphates, phosphonates, phosphines, amine salts or metal salts of those compounds; sulfur- and phosphorus-containing antiwear agents such as thiophosphites, thiophosphates, thiophosphonates, amine salts or metal salts of those compounds.

[0186] The antiwear agent may be present in an amount of 0 to 3 wt %, preferably 0.1 to 2 wt %, based on the total weight of the polymer-inorganic nanoparticle composition.

[0187] Preferred friction modifiers may include mechanically active compounds such as molybdenum disulfide, graphite (including graphite fluoride), poly(trifluoroethylene), polyamide, polyimide; compounds that form an adsorption layer, such as long-chain carboxylic acids, fatty acid esters, ethers, alcohols, amines, amides, imides; compounds that form a layer via a tribochemical reaction, such as saturated fatty acids, phosphates; compounds that form a polymeric layer, such as ethoxylated dicarboxylic acid partial esters, functionalized poly(meth)acrylates, unsaturated fatty acids, sulfided olefins and organometallic compounds, such as molybdenum compounds (molybdenum dithiophosphates and molybdenum dithiocarbamates MoDTC) and their combinations with ZnDTP, copper-containing organic compounds.

[0188] Some of the compounds listed above may fulfil more than one function. For example, ZnDTP is primarily an anti-friction additive and an extreme pressure additive, but also has the properties of an antioxidant and a corrosion inhibitor (here: metal passivator / deactivator).

[0189] The additives specified above are described in detail in particular in T. Mang, W. Dresel (eds.): "Lubricants and Lubrication", Wiley-VCH, Weinheim 2001; RM Mortier, ST Orszulik (eds.): "Chemistry and Technology of Lubricants".

[0190] Preferably, the total concentration of the one or more additives (D) is up to 20 wt%, more preferably 0.05 wt% to 15 wt%, based on the total weight of the polymer-inorganic nanoparticle composition.

[0191] Preferably, the amounts of components (A) to (D) total 100 wt %, based on the total weight of the polymer-inorganic nanoparticle composition.

[0192] Experimental Section

[0193] The present invention is described in further detail hereinafter with reference to Examples and Comparative Examples, without intending to limit the scope of the present invention.

[0194] Abbreviation

[0195] C1AMA C1-alkyl methacrylate (methyl methacrylate; MMA)

[0196] C4 AMA C4-alkyl methacrylate (n-butyl methacrylate; BMA)

[0197] C 12-14 AMA Methacrylate C 12-14 -Alkyl esters (lauryl methacrylate; LMA)

[0198] C 12-15 AMA Methacrylate C 12-15 -Alkyl ester (dodecyl pentadecyl methacrylate; DPMA)

[0199] DMAEMA Dimethylaminoethyl methacrylate

[0200] DMAPMA N-3-Dimethylaminopropyl methacrylamide

[0201] Oxa(meth)acrylic acid Oxazolidinyl ethyl ester

[0202] MEMO 3-(Trimethoxysilyl)propyl methacrylate

[0203] CTA Chain Transfer Agent

[0204] f 支链 Degree of branching (mol%)

[0205] M n Number average molecular weight

[0206] M w Weight average molecular weight

[0207] PDI polydispersity index, molecular weight distribution calculated via Mw / Mn

[0208] NB3020 3020, a Group III base oil from Neste, with a KV40 of 7.7 cSt (ASTM D-445) and a flash point of >150°C (ASTM D-93)

[0209] NB3043 3043, a Group III base oil from Neste, with a KV40 of 20 cSt (ASTM D-445) and a flash point of >220°C (ASTM D-92)

[0210] TetrabutaneTetrabutane (branched C 16 and C 20 Saturated hydrocarbon isomers), with a KV40 of 4.2 cSt (ASTM D-445) and a flash point of 124°C (ASTM D-93)

[0211] PAO synthetic polyalphaolefin, Group IV base stock, with a KV40 of 5.2 cSt (ASTM D-445) and a flash point of 130°C (ASTM D-93)

[0212] Al2O3 1 Pyrolysis Al2O3 (surface area: 85-115m 2 / g, according to ISO 9277)

[0213] Al2O3 2 Pyrolysis Al2O3 (surface area: 55-75m 2 / g, according to ISO 9277)

[0214] TiO2 1 Pyrolysis TiO2 (surface area: 35-65m 2 / g, according to ISO 9277)

[0215] TiO2 2 Pyrolysis TiO2 (surface area: 75-105m 2 / g, according to ISO 9277)

[0216] Preparation of the polymer compound (B) according to the present invention

[0217] The polymer number average molecular weight (Mn) was measured by gel permeation chromatography (GPC) calibrated using polymethyl methacrylate (PMMA) calibration standards as described above. Tetrahydrofuran (THF) was used as the eluent.

[0218] Example of polymer compound (B) Polymer 1 (P1): Preparation of the amine-containing copolymer according to the invention

[0219] 200 g of NB3043, 11.34 g of n-3-dimethylaminopropyl methacrylamide (DMAPMA), 272.21 g of lauryl methacrylate (C12-14AMA), 5.53 g of n-dodecyl mercaptan (n-DDM), 5.53 g of 2-ethylhexyl thioglycolate (TGEH) were charged into a 2-liter 4-necked round bottom flask. The reaction mixture was stirred using a C-stirring bar, inerted with nitrogen, and heated to 90°C. Once the reaction mixture reached the set point temperature, 2.83 g of tert-butyl peroctanoate was fed into the reactor within 2 hours. After 2 hours, the mixture was heated to 100°C, and after reaching the set point, 1.42 g of tert-butyl per-2-ethylhexanoate and 1.13 g of tert-butyl peroxypivalate were fed within 1 hour. Residual monomers were measured by gas chromatography to ensure good monomer conversion. The polymer obtained had a number average molecular weight Mn (PMMA standard sample) of 6,500 g / mol.

[0220] As an example of polymer compound (B), polymer 2 (P2) - according to the invention contains Copolymers of oxazolidinyl preparation

[0221] The preparation was the same as for polymer 1. The final polymer obtained had a number average molecular weight Mn of 9,400 g / mol (PMMA standard sample).

[0222] Example of polymer compound (B) Polymer 3 (P3) - Preparation of an amine-containing copolymer according to the invention

[0223] The preparation was the same as for polymer 1. The final polymer obtained had a number average molecular weight Mn of 29,000 g / mol (PMMA standard sample).

[0224] Example of polymer compound (B) Polymer 4 (P4) - Preparation of the amine-containing copolymer according to the invention

[0225] The preparation was the same as for polymer 1. The final polymer obtained had a number average molecular weight Mn of 65,000 g / mol (PMMA standard sample).

[0226] Example of polymer compound (B) Polymer 5 (P5) - Preparation of the amine-containing copolymer according to the invention

[0227] The preparation was identical to polymer 1. In this case, the polymerization set point temperature was 80° C. instead of 90° C. and 100° C. The final polymer obtained had a number average molecular weight Mn of 15,000 g / mol (PMMA standard).

[0228] Example of polymer compound (B) Polymer 6 (P6) - Preparation of a silicon-containing copolymer according to the invention

[0229] The preparation was the same as for polymer 1. The final polymer obtained had a number average molecular weight Mn of 7,100 g / mol (PMMA standard sample).

[0230] For Examples P1, P2, P3, P4, P5 and P6, the monomer components add up to 100%. The amounts of initiators and chain transfer agents are given relative to the total amount of monomers. Table 4 below shows the monomer compositions and reactants for the preparation of polymers P1, P2, P3, P4, P5 and P6, as well as their final characterization.

[0231]

[0232] Preparation of polymer-inorganic nanoparticle composition according to the present invention

[0233] Dispersion IE1:

[0234] 10g of pyrolyzed Al2O3 1 (surface area: 85-115m 2 / g, according to ISO 9277) particles were added to a solution of 85 g of synthetic PAO containing 5 g of P2, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 219 nm.

[0235] Dispersion IE2:

[0236] 10g of pyrolyzed Al2O3 1 (surface area: 85-115m2 / g, according to ISO 9277) particles were added to a solution of 85 g NB3020 containing 5 g P1, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 205 nm.

[0237] Dispersion IE3:

[0238] 10g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were added to a solution of 85 g NB3020 containing 5 g P1, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 182 nm.

[0239] Dispersion IE4:

[0240] 10g of pyrolyzed Al2O3 1 (surface area: 85-115m 2 / g, according to ISO 9277) particles were added to a solution of 85 g of tetrabutane containing 5 g of P3, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 172 nm.

[0241] Dispersion IE5:

[0242] 10g of pyrolyzed Al2O3 1 (surface area: 85-115m 2 / g, according to ISO 9277) particles were added to a solution of 85 g of tetrabutane containing 5 g of P1, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 189 nm.

[0243] Dispersion IE6:

[0244] 10g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were added to a solution containing 5 g of P1 in 85 g of tetrabutane, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 30 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 244 nm.

[0245] Dispersion IE7:

[0246] 10g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were added to a solution of 85 g of tetrabutane containing 5 g of P3, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 30 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 266 nm.

[0247] Dispersion IE8:

[0248] 10g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were added to a solution of 85 g NB3020 oil containing 5 g P1, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasound generator) for 30 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 234 nm.

[0249] Dispersion IE9:

[0250] 10g of pyrolyzed Al2O3 2 (surface area: 55-75m 2 / g, according to ISO 9277) particles were added to a solution of 85 g NB3020 containing 5 g P1, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasound generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 219 nm.

[0251] Dispersion IE10:

[0252] 10g of pyrolyzed Al2O3 1 (surface area: 85-115m 2 / g, according to ISO 9277) particles were added to a solution of 85 g NB3020 containing 5 g P4, while this mixture was ground with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 60 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 246 nm.

[0253] Dispersion IE11:

[0254] First, a pre-dispersion was prepared. 20.0 kg of pyrolyzed TiO21 (surface area: 35-65 m 2 / g, according to ISO 9277) was added to a mixture of 54kg NB3043 containing 6kg P5. This dispersion was treated in a dissolver for 30 minutes, keeping the dissolver disk rotating at a speed of about 20m / s. This pre-dispersion was treated using ultra-high pressure technology (jet milling equipment SuginoUltimaizer HJP-25050). The pre-dispersion was set at a pressure of 2,500 bar using a jet mill and processed twice. Finally, the dispersion was diluted to a solid content of 15wt% TiO2 1 using NB3043. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 225nm.

[0255] Dispersion IE12:

[0256] First, a pre-dispersion was prepared. 5.0 kg of pyrolyzed TiO22 (surface area according to ISO 9277: 75-105 m 2 / g) was added to a mixture of 43.0 kg NB3043 containing 2 kg P6. This dispersion was processed in a dissolver for 30 minutes, keeping the dissolver disk rotating at a speed of about 20 m / s. This pre-dispersion was processed using ultra-high pressure technology (jet milling equipment SuginoUltimaizer HJP-25050). The pre-dispersion was set at a pressure of 1,400 bar using a jet mill and processed twice. The process was then repeated at a pressure of 2,500 bar. Particle size distribution (measured in Tegosoft DEC oil using dynamic light scattering equipment LA-950, Horiba Ltd., Japan) showed a d99 value of 234 nm.

[0257] Dispersion IE13:

[0258] First, a pre-dispersion was prepared. 20.0 kg of pyrolyzed TiO22 (surface area according to ISO 9777: 75-105 m 2 / g) was added to a mixture of 53kg NB3043 containing 7kg P5. This dispersion was treated in a dissolver for 30 minutes, keeping the dissolver disk rotating at a speed of about 20m / s. This pre-dispersion was treated using ultra-high pressure technology (jet milling equipment SuginoUltimaizer HJP-25050). The pre-dispersion was set at a pressure of 2,500 bar using a jet mill and processed twice. Finally, the dispersion was diluted to a solid content of 15wt% TiO2 2 using NB3043. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 183nm.

[0259] Preparation of Comparative Example

[0260] Dispersion CE1:

[0261] 1g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were added to a solution of 18 g of NB3043 oil, and this mixture was treated with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasound generator) for 30 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 1,927 nm.

[0262] Dispersion CE2:

[0263] 1g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were added to a solution of 18 g of tetrabutane, and this mixture was treated with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasound generator) for 30 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 1,850 nm.

[0264] Dispersion CE3:

[0265] 0.46 g of pyrolyzed Al2O3 1 (surface area: 85-115 m 2 / g, according to ISO 9277) particles were added to a solution of 18 g of tetrabutane, while this mixture was treated with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasound generator) for 60 minutes. The particle size distribution (measured in TegosoftDEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 1,867 nm.

[0266] Dispersion CE4:

[0267] 2g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were mixed with 1 g of oleyl alcohol. After adding 16 g of tetrabutane, this mixture was treated with ultrasound (ultrasonic processor UP400S, with 400 watts, 24 kHz, with Ti-ultrasonic generator) for 30 minutes. The particle size distribution (measured in TegosoftDEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 1,457 nm.

[0268] Dispersion CE5:

[0269] 2g of pyrolyzed TiO2 1 (surface area: 35-65m 2 / g, according to ISO 9277) particles were mixed with 1g of Triton X-100. After adding 16g of NB3020, this mixture was treated with ultrasound (ultrasonic processor UP400S, with 400 watts, 24kHz, with Ti-ultrasound generator) for 30 minutes. The particle size distribution (measured in Tegosoft DEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 1,608nm.

[0270] Dispersion CE6:

[0271] 1g of pyrolyzed Al2O3 1 (surface area: 85-115m 2 / g, according to ISO 9277) particles were mixed with 0.5 g of oleyl alcohol. After adding 16 g of tetrabutane, this mixture was treated with ultrasound (ultrasound processor UP400S with 400 watts, 24 kHz, with Ti-ultrasound generator) for 60 minutes. The particle size distribution (measured in TegosoftDEC oil using a dynamic light scattering device LA-950, Horiba Ltd., Japan) showed a d99 value of 1,635 nm.

[0272] Dynamic Light Scattering (DLS)

[0273] The particle size distribution was measured in Tegosoft DEC oil using a dynamic light scattering apparatus LB-500 manufactured by HORIBA LTD.

[0274] Dynamic light scattering (DLS) is a physics technique that can be used to determine the particle size distribution curve of small particles in suspension or polymers in solution. This equipment can be used to measure the particle size of dispersed materials (such as inorganic nanoparticles or polymer spheres) in the range of 3nm to about 6μm. The measurement is based on the Brownian motion of particles within the medium and the scattering of incident laser light due to the difference in refractive index of liquid and solid materials.

[0275] The obtained value is the hydrodynamic diameter of the corresponding sphere of the particle. The values ​​d50, d90 and d99 are common standards for discussion because these describe the hydrodynamic diameter of the particle, below which 50%, 90% or 99% of the particles are within the particle size distribution. The lower these values ​​are, the better the particle dispersion is. Monitoring these values ​​can give clues about the stability of the particle dispersion. If the value increases significantly, the particles are not stable enough and may tend to agglomerate and deposit over time, resulting in a lack of stability. Depending on the viscosity of the medium, it can be said that a d99 value of <500nm (e.g. for Nexbase base oil) is an indication of a stable dispersion because the particles remain suspended over time.

[0276] Dynamic viscosity

[0277] The dynamic viscosity was measured using a Physica MCR 300 from Anton Paar using the rotational viscosity method and a single-gap cylinder CC 27.

[0278] The motor of the viscometer drives the oscillator weight in the fixed cup. The rotation speed of the oscillator weight is preset and generates a certain motor torque required to rotate the measuring oscillator weight. This torque must overcome the viscous forces of the test material and is therefore a measure of its viscosity.

[0279] In 100s -1 The data are measured at shear rates and 23°C.

[0280] Visual appearance / stability

[0281] Each sample was subjected to stability test by diluting a small amount of concentrate to 1 wt % and 0.1 wt % inorganic nanoparticle solution (i.e., wt % of particles). The diluent was prepared by blending the concentrate in a 50 mL glass scintillator for 1 hour at room temperature. Each diluent was placed in a 5 ml glass vial and allowed to stand at room temperature. After blending, one week, and four weeks, the vial was checked for signs of sedimentation. Sedimentation was divided into 5 categories: no sedimentation (no particles settled at the bottom of the vial), slight sedimentation (some particles began to settle at the bottom of the vial), medium sedimentation (thin layer at the bottom of the vial), almost complete sedimentation (almost all particles settled and the supernatant became clear).

[0282] For dispersions containing any kind of particles, sedimentation over time is a clear indicator of stability. Over time, the particles will settle to the floor of the vial. This usually depends on their size, mass and the viscosity of the base fluid. A stable dispersion is characterized by the fact that the particles are uniformly dispersed in the medium and stabilized by known mechanisms.

[0283] Therefore, the stability of the nanoparticles in the dispersion is an obvious prerequisite for the heat transfer properties of the nanofluid. Compared with the prior art heat transfer nanofluids, the examples of the invention provided below show higher stability with different stability tests and good thermal conductivity over a long period of time (see Tables 5 and 6). Therefore, the following stability tests were not only carried out at room temperature, which is usually more easily achievable, but also at higher temperatures and longer periods of time (e.g. 16 hours at 100°C, see Tables 7 and 8), which simulates the application of cooling electric motors with a maximum temperature of about 100°C.

[0284] Comparative Examples 1 to 3 (Comp. 1-3) are simple mixtures of inorganic nanoparticles in a base fluid that are not chemically modified with any kind of surfactant or additive. Comparative Examples 4 to 6 (Comp. 4-6) are patent examples from US8850803B2.

[0285]

[0286]

[0287] Stability test at 100°C (viscosity change)

[0288] The corresponding dispersions of Table 6 were taken and diluted to 1 wt %, 5 wt % and 10 wt % concentrations of nanoparticles in the dispersion (see Table 7). The dynamic viscosity and thermal conductivity of these samples were measured. The aliquots were filled into glass vials and stored in an oven at 100° C. for 16 hours (overnight). After the dispersions were cooled to room temperature, their dynamic viscosity and thermal conductivity were measured again.

[0289] During storage at 100 °C, the dynamic processes between the particles and the fluid medium are enhanced due to the higher kinetic energy, which may lead to reagglomeration and / or precipitation of the nanoparticles in the dispersion. Therefore, an increase in viscosity of more than 10% means that the stability of the dispersion cannot be achieved.

[0290] As shown in Table 7 below, the inventors of the present invention were able to prepare nanoparticle dispersions for use as heat transfer fluids that not only have good thermal conductivity but also good stability given the requirements of a given heat transfer fluid.

[0291] In contrast, even at room temperature, the comparative examples could not be tested due to their instability after one day of storage. Therefore, stability tests at elevated temperatures (e.g. 16 hours at 100° C.) were not even possible, which simulates the use of cooling electric motors with a maximum temperature of about 100° C.

[0292]

[0293] Thermal conductivity was determined by LAMBDA equipment (Flucon GmbH)

[0294] The determination of thermal conductivity is carried out by the hot wire method. The hot wire of LAMBDA is used as a heat source and at the same time as a transducer. To increase the temperature, the hot wire is subjected to a constant measuring current; when the surrounding medium heats up, the resistance of the hot wire will change according to the thermal viscosity of the surrounding medium. Therefore, the voltage change in the hot wire indicates the temperature change occurring in the surrounding medium. The measuring range is 10-2000mW / m*K.

[0295] After thematicization, the data were measured via a PT 100 platinum thermometer of the measuring device in a metal block thermostat at 40° C. and 100° C. These temperatures were chosen because they are of interest for important applications.

[0296] As shown in Table 8 below, the use of the polymer-inorganic nanoparticle composition according to the present invention as a heat transfer fluid is advantageous because not only is the stability of the inorganic nanoparticles in the dispersion maintained over time, as shown in Table 6, but also when used as a heat transfer fluid, the polymer-inorganic nanoparticle composition of the present invention provides improved thermal conductivity compared to the prior art heat transfer base oil reference. In addition, as shown in Table 7, the addition of inorganic nanoparticles does not have a large effect on the change in viscosity, which is unexpected and advantageous.

[0297]

[0298] As shown in the above experimental section, it can be concluded that the comparative dispersions cannot be used as heat transfer nanofluids since they do not even meet the stability standard test.

[0299] In contrast, it was demonstrated that the polymer-inorganic nanoparticle compositions of the present invention comprising metal or metalloid oxide nanoparticles, metal or metalloid nitride nanoparticles, metal or metalloid carbide nanoparticles or mixtures thereof are stable for a long period of time under conditions close to those used as heat transfer fluids (16 hours at 100° C.) without losing dispersion stability (viscosity) and thermal conductivity.

[0300] Load capacity test:

[0301] Dispersion IE13 was taken and diluted in NB 3043 to a nanoparticle concentration of 0.5 wt% in the dispersion (IE13-0.5).

[0302] The FZG wear test was carried out according to DIN ISO 14635-2 at 90° C. (A10 / 16.6R / 90) with dispersion IE13-0.5. This resulted in a pass load stage 12 with a pass load stage of 0 mm. 2 and a pinion weight loss of 6 mg and a wheel weight loss of 12 mg, for a total weight loss of 18 mg. The highest pass load station in this test is 12. It can therefore be shown that the inorganic nanoparticle composition according to the present invention can provide excellent load capacity performance. High failure load stations are required to protect the gears from damage during their entire life. Typical transmission systems have a failure load station (FLS) of 8 to 10. However, this can only be achieved by using sulfur-containing additives which lead to aging problems as well as high copper corrosion. According to DIN ISO 14635-2, a pass load station is reached after 21,700 exposures without damaging the teeth of the gear. In this test, the Group III base oil NB 3043 alone has an FLS of 4.

[0303] Cu-corrosion test:

[0304] Copper corrosion data collected using dispersion IE13-0.5 according to ASTM D130@160°C:

[0305] At 160℃ for 3h: Result 1b

[0306] At 160℃ for 72h: Result 1b

[0307] At 160℃ for 168h: Result 1b

[0308] The copper strip is immersed in oil for a specified time and temperature. After the test, the copper strip shows a certain color change. The color change is directly related to copper corrosion. Copper corrosion is classified according to a table representing the different colors of the strip from 1a to 4c. The value of 1b indicates slight rusting, which confirms the absence of copper corrosion.

[0309] Filterability test:

[0310] The filterability of dispersion IE13-0.5 was tested according to the Scania filtration test STD 4263, 2009-04 method, which indicates the filterability of lubricating oils (e.g. transmission fluids). The higher the FI and FII values, the better the filterability. The test according to this method is successfully passed if the FII value exceeds 90%. In the filterability test according to this method, dispersion IE13-0.5 has a FI value of 96.4% and a FII value of 91.5%.

[0311] The FZG wear test and copper corrosion test show the advantages of the composition according to the invention. It is unexpected to have excellent load carrying capacity in a transmission fluid without any copper corrosion.

[0312] For clarity, Table 9 below summarizes the results obtained with dispersion IE13-0.5 in the FZG wear, copper corrosion and Scania filtration tests.

[0313] Table 9:

[0314] Test methods IE13-0.5 FZG(A10 / 16.6R / 90) >12 Cu corrosion ASTM D-130 3h / 72h / 168h@160℃ 1b / 1b / 1b Scania STD 4263, 2009-04 (5μm pore size) FI: 96.4%; FII: 91.5%

Claims

1. Use of a polymer-inorganic nanoparticle composition as a heat transfer fluid in a battery or other electrical device system, wherein the polymer-inorganic nanoparticle composition is obtained by grinding a mixture comprising one or more inorganic nanoparticle compounds (A) and one or more polymer compounds (B), (A) wherein the one or more inorganic nanoparticle compounds are selected from metal or metalloid oxide nanoparticles, metal or metalloid nitride nanoparticles, metal or metalloid carbide nanoparticles or mixtures thereof, and (B) wherein the one or more polymer compounds are obtained by polymerizing a monomer composition comprising: a) 1% to 35% by weight, based on the total weight of the monomer composition, of one or more functional monomers selected from the list consisting of: a1) aminoalkyl (meth)acrylates and aminoalkyl (meth)acrylamides; a2) nitriles of alkyl(meth)acrylic acids and other nitrogen-containing alkyl(meth)acrylates; a3) (meth)acrylates of ether alcohols; a4) Oxiranyl alkyl (meth)acrylate; a5) phosphorus-, boron- and / or silicon-containing alkyl (meth)acrylates; a6) heterocycloalkyl (meth)acrylate; a7) vinyl halides; a8) vinyl esters; a9) vinyl monomers containing aromatic groups; a10) heterocyclic vinyl compounds; a11) vinyl and prenyl ethers; a12) methacrylic acid and acrylic acid, b) 65 to 99 wt. % of one or more alkyl (meth)acrylate monomers, based on the total weight of the monomer composition, wherein each of the alkyl groups of the one or more alkyl (meth)acrylate monomers is independently linear, cyclic or branched and contains 1 to 40 carbon atoms, and wherein the weight ratio of the one or more inorganic nanoparticle compounds (A) to the one or more polymer compounds (B) is from 9:1 to 1:

5.

2. The method according to claim 1, wherein the one or more polymer compounds (B) have a number average molecular weight (Mn) of 2,000 to 150,000 g / mol as determined by gel permeation chromatography using polymethyl methacrylate calibration standards and tetrahydrofuran as eluent.

3. The use according to claim 2, wherein the one or more polymer compounds (B) have a number average molecular weight (Mn) of 5,000 to 100,000 g / mol as determined by gel permeation chromatography using polymethyl methacrylate calibration standards and tetrahydrofuran as eluent.

4. The use according to claim 2, wherein the one or more polymer compounds (B) have a number average molecular weight (Mn) of 5,000 to 80,000 g / mol as determined by gel permeation chromatography using polymethyl methacrylate calibration standards and tetrahydrofuran as eluent.

5. The method according to claim 1, wherein the one or more alkyl (meth) acrylate monomers b) comprise b1) 0 to 20% by weight of one or more alkyl (meth)acrylates of the formula (I), as first component b): (I) Where R is hydrogen or methyl, R 1 means a linear, branched or cyclic alkyl residue containing 1 to 8 carbon atoms, based on the total weight of the monomer composition, b2) 45 to 99% by weight of one or more alkyl (meth)acrylates of the formula (II), as second component b): (II) Where R is hydrogen or methyl, R 2 means a linear, branched or cyclic alkyl residue containing 9 to 15 carbon atoms, based on the total weight of the monomer composition, b3) 0 to 30% by weight of one or more alkyl (meth)acrylates of the formula (III), as third component b): (III) Where R is hydrogen or methyl, R 3 It means a linear, branched or cyclic alkyl residue containing from 16 to 40 carbon atoms, based on the total weight of the monomer composition.

6. The use according to claim 5, wherein R 1 It means a linear, branched or cyclic alkyl radical containing 1 to 5 carbon atoms.

7. The use according to claim 5, wherein R 1 It means a linear, branched or cyclic alkyl radical containing 1 to 4 carbon atoms.

8. The use according to claim 5, wherein R 2 This refers to a linear, branched or cyclic alkyl radical containing 12 to 15 carbon atoms.

9. The use according to claim 5, wherein R 3 It means a linear, branched or cyclic alkyl radical containing 16 to 30 carbon atoms.

10. The use according to claim 5, wherein R 3 It means a linear, branched or cyclic alkyl radical containing 16 to 22 carbon atoms.

11. The use according to any one of claims 1 to 4, wherein the amounts of monomers a) and b) of the monomer composition add up to 100% by weight, based on the total weight of the monomer composition.

12. The use according to any one of claims 1 to 4, wherein the weight ratio of the one or more inorganic nanoparticle compounds (A) to the one or more polymer compounds (B) is from 9:1 to 1:

2.

13. The use according to claim 12, wherein the weight ratio of the one or more inorganic nanoparticle compounds (A) to the one or more polymer compounds (B) is from 3:1 to 1:

1.

14. The method according to claim 1, wherein the monomer component a) is selected from aminoalkyl (meth)acrylates a1) or aminoalkyl (meth)acrylamides a1) or silicon-containing alkyl (meth)acrylates a5) or heterocycloalkyl (meth)acrylates a6).

15. The method according to claim 14, wherein the monomer component a) is selected from N-(3-dimethylaminopropyl)methacrylamide, 2-dimethylaminoethyl (meth)acrylate, 3-(trimethoxysilyl)propyl methacrylate, 3-(triethoxysilyl)propyl methacrylate or (meth)acrylate. Oxazolidinyl ethyl ester.

16. The use according to any one of claims 1 to 4, wherein the inorganic nanoparticle compound (A) is selected from titanium dioxide, aluminum oxide or a mixture thereof.

17. The use according to any one of claims 1 to 4, wherein the polymer-inorganic nanoparticle composition further comprises a base fluid (C) having a kinematic viscosity at 40°C according to ASTM D445 of 3 cSt to 30 cSt and a flash point according to ASTM D-93 of above 110°C.

18. The use according to claim 17, wherein the polymer-inorganic nanoparticle composition further comprises a base fluid (C) having a kinematic viscosity at 40°C according to ASTM D445 of 3 to 25 cSt.

19. The use according to claim 17, wherein the base fluid is selected from the list consisting of: API Group I base oil, API Group II base oil, API Group III base oil, API Group IV base oil, API Group V base oil or mixtures thereof.

20. The use according to claim 17, wherein the polymer-inorganic nanoparticle composition comprises 80 to 99.9 wt% of the base fluid (C) and 0.1 to 20 wt% of (A) and (B), based on the total weight of the polymer-inorganic nanoparticle composition.

21. The use according to claim 20, wherein the polymer-inorganic nanoparticle composition comprises 85 to 99.9 wt% of the base fluid (C) and 0.1 to 15 wt% of (A) and (B), based on the total weight of the polymer-inorganic nanoparticle composition.

22. The use according to claim 20, wherein the polymer-inorganic nanoparticle composition comprises 88 to 99.5 wt% of the base fluid (C) and 0.5 to 12 wt% of (A) and (B), based on the total weight of the polymer-inorganic nanoparticle composition.

23. The use according to claim 17, wherein the amounts of (A), (B) and (C) add up to 100 wt. %, based on the total weight of the polymer-inorganic nanoparticle composition.

24. The use according to any one of claims 1 to 4, wherein the polymer-inorganic nanoparticle composition comprising one or more nanoparticles (A), one or more polymer compounds (B) and optionally a base fluid (C) is prepared via ultrahigh pressure technology.

25. The method according to claim 1, characterized in that The heat transfer fluid further comprises an additive selected from the group consisting of antioxidants, antiwear additives, extreme pressure additives, pour point depressants, demulsifiers, emulsifiers, corrosion inhibitors, metal passivators, rust inhibitors, electrostatic discharge inhibitors, defoamers, seal fixatives or seal compatibilizers, friction modifiers, dyes, or mixtures thereof.

26. The use according to any one of claims 1 to 4, wherein the electrical equipment system is selected from the group consisting of electric motors, electric vehicle transmissions, power transformers, capacitors, fluid-filled power cables and computers.

27. The use according to claim 26, wherein the electrical equipment system is a fluid filled drive line.

28. Use according to claim 26, wherein the electrical equipment system is power electronics.

Citation Information

Patent Citations

  • Heat transfer fluids and corrosion inhibitor formulations for use thereof

    US20170009120A1

  • Auxiliary power and emission-control system using vented gaseous fuel recovery and method

    US8850803B2

  • Thermally conductive nanocomposition and method of making the same

    WO2013115925A1

  • Heat transfer-fluid with electrical insulating properties

    WO2014106556A1

  • Polymeric-inorganic particles useful as lubricant additives

    WO2018019783A1

Cited By

  • Biodegradable nanofluid heat exchange agent

    CN121518116A